Analýza sociálních sítí - využití v praxi - Panuš, Jan (Univerzita Pardubice, 2011)
Social networks are phenomenon of these days. We can usually use it for web application like a Facebook etc. Subject of this paper is to bring different perspective on social networks and its analysis. We will show some basic metrics of social networks analysis on particular problem which is dynamic analysis of government of the Czech Republic.
Keywords: social networks; analysis; methods; government of the Czech Republic